Bob books. Stage 2: Emerging reader, Animal stories - Kertell, Lynn Maslen (Kertell, Lynn Maslen. Bob books., 2019)
"In Bob Books First stories you will find twelve easy-to-read and humorous books. Perfect for emerging readers, this set including kid-approved stories that progress gently through graded reading levels A, B, and C. With one-syllable words and short vowels, Bob Books First stories is a fun confidence builder, especially for kids in Kindergarten"--Publisher's description.